Association of cell death mechanisms and fibrosis in visceral white adipose tissue with pathological alterations in the liver of morbidly obese patients with NAFLD - Anna-Sophia Leven (Taylor & Francis Group, 2021)
The role of visceral white adipose tissue (vWAT) in the progression of non-alcoholic liver disease (NAFLD) with its sub entities non-alcoholic fatty liver and steatohepatitis (NAFL; NASH) is underinvestigated. We thus explored mechanisms of fibrosis and regulated cell death in vWAT and liver tissue. In NAFLD, women displayed significantly more fibrosis in vWAT than men, and collagen 1α mRNA expression was significantly upregulated. The degrees of fibrosis in vWAT and liver tissue correlated significantly. The size of vWAT-resident adipocytes in NAFLD correlated negatively with the local degree of fibrosis. The extent of apoptosis, as measured by circulating M30, positively correlated with the degree of fibrosis in vWAT; necrosis-associated HMGB1 mRNA expression was significantly downregulated in vWAT and liver tissue; (iii) necroptosis-related RIPK-3 mRNA expression was significantly upregulated in vWAT; and autophagy-related LC3 mRNA expression was significantly downregulated in vWAT, while upregulated in the liver. Thus, the different cell death mechanisms in the vWAT in NAFLD are regulated independently while not ruling out their interaction. Fibrosis in vWAT may be associated with reduced adipocyte size and thus partially protective against NAFLD progression. Abbreviations: ATG5: autophagy related 5; BAS: bariatric surgery; BMI: body mass index; ELISA: enzyme-linked immunosorbent assay; EtOH: ethanol; FFAs: free fatty acids; HCC: hepatocellular carcinoma; HMGB1: high-mobility group box 1 protein; IHC: immunohistochemistry; IL: interleukin; LC3: microtubule-associated proteins 1A/1B light chain 3B; M30: neoepitope K18Asp396-NE displayed on the caspase-cleaved keratin 18 fragment; M65: epitope present on both caspase-cleaved and intact keratin 18; NAFL: non-alcoholic fatty liver; NAFLD: non-alcoholic fatty liver disease; NAS: NAFLD activity score; NASH: non-alcoholic steatohepatitis; NLRP3: nucleotide-binding oligomerization domain, leucine-rich repeat and pyrin domain containing 3; qRT-PCR: quantitative real-time polymerase-chain reaction; r: Pearson’s correlation coefficient (r); rs: Spearman’s rank correlation coefficient; RIPK3: receptor-interacting serine/threonine-protein kinase 3; T2DM: type 2 diabetes mellitus (T2DM); TUNEL: terminal deoxynucleotidyl transferase-mediated dUTP nick-end labelling; vWAT: visceral WAT; WAT: white adipose tissue